Affinity‐Based Isolation and One‐Pot Analysis of Extracellular Vesicles from Biofluids Using Phase Separated Zwitterionic Coacervates - Francesca Torrini; Roberto Frigerio; Jonathan Garlipp; Philippe Lenzen; Karl Normak; Carolina Paganini; Marina Cretich; Alessandro Gori; Paolo Arosio (Advanced Science)
Abstract Extracellular vesicles (EVs) hold promise for liquid biopsy and drug delivery applications. However, their heterogeneous nature poses challenges for efficient and selective isolation from complex biofluids. Here, an isolation method based on phase‐separated zwitterionic (ZW) coacervates is developed. These coacervates form over a wide range of pH values and ionic strengths, ensuring compatibility with all biofluids. They exhibit antifouling properties that minimize nonspecific binding, allowing for the selective isolation of EVs from biofluids upon functionalization of the polymer with a suitable affinity probe, as proved here with a membrane‐sensing peptide. This strategy is applied to pull down, concentrate, and release EVs from urine samples with high yields while retaining their structural integrity. This approach effectively separates EVs from lipoproteins, a challenging task for conventional separation techniques. The power of the approach is demonstrated as a preparative step for downstream analysis and as a one‐pot assay to profile EV biomarkers in complex fluids. The latter application, implemented here with flow cytometry, significantly streamlines pre‐analytical workflows. Thus, functionalized ZW coacervates represent an effective strategy for the selective isolation and direct analysis of EVs from complex mixtures, paving the way for advances in large‐scale manufacturing and diagnostics.